Right versus left Colon cancer: Is there a difference in outcomes? - Aris Plastiras; Evangelia Iosif; Georgia Georgiou; Amyn Haji; Asif Haq; Savvas Papagrigoriadis; Joseph W. Nunoo-Mensah (World Journal of Colorectal Surgery)
Background: Colorectal cancer is a major healthcare problem due to its high prevalence and mortality rates. Objective: The objective of the study is to delineate the relationship between the location of the colon cancer and the outcomes. Design: This is a retrospective, single-center study including patients diagnosed with right and left colon cancer from January 2010 to December 2015. Setting: Patients with no rectal or synchronous metastatic disease were included in the study. Diagnosis was confirmed following a computed tomography and colonoscopy. Patients and Methods: Four hundred and seventy-five patients with colon cancer were included; 226 right-sided tumors (RCC) and 249 with left-sided colon cancer (LCC) underwent surgery. Main Outcome Measures: We compared right- and left-sided tumors in terms of epidemiological, histological, clinical, and perioperative characteristics, and we also attempted to determine whether there is a difference in the overall and per stage survival. Sample Size: Four hundred and seventy-five patients with colon cancer. Results: Patients with colon cancer were analyzed, 226 (47.5%) with RCC and 249 (52.4%) with LCC underwent surgery. Patients with RCC were more likely to be women, older, and with more comorbidities. Furthermore, RCC were more likely to be poorly differentiated (29.65%, P < 0.001) and more locally advanced at the time of diagnosis (P < 0.001). Controlling the differentiation for each stage, there was no statistical significant difference between left and right survival and recurrence (P > 0.05). When stratified according to tumor stage, Stage II LCC had better overall survival (odds ratio [OR], 1.694, 95% confidence interval [CI], 1.015, 2.827) and Stage III LCC had a better overall survival (OR, 1.403, 95% CI, 1.007, 2.143), disease-free survival (OR, 1.293, 95% CI, 1.011, 1.714), and less cancer-related deaths (OR, 0.282, 95% CI, 0.080, 1.000). Conclusions: Comparing similar stages, patients with LCC appear to have better oncological outcomes irrespective of tumor differentiation. Limitations: Single-center, retrospective study without excluding patients with hereditary cancers. Oncological biomarkers were not available in all patients, and further analysis was not performed.